RATS as a Symbol of Corruptors in the Conceptualization of Dark Art Paintings Utilizing Drawing Techniques - Pinem, Andreas Christ Daniel; Muslim, Muslim (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
This study investigates the utilization of rats as symbolic representations of corruptors within the context of creating dark art paintings employing drawing techniques. Rats were selected due to their association with greed, cunning, and destructive nature, which effectively encapsulate corrupt behavior. The dark art movement serves as a visual approach to convey the moral and societal consequences of corruption, with a particular emphasis on evoking a somber and symbolic atmosphere. Drawing techniques that prioritize intricate line details and shadow play are employed to explore the emotional and narrative elements of the artwork. The media utilized include pencils, drawing pens, charcoal, and ink on watercolor paper. The outcomes of the artwork creation demonstrate that the incorporation of rat symbols within dark art compositions can effectively convey messages of social criticism regarding corruption. The amalgamation of dark elements, dramatic textures, and rat symbolism results in works that not only possess aesthetic value but also serve as a medium of reflection and education for the community. The drawing technique offers flexibility in conveying visual details, thereby enhancing the representation of the underlying messages conveyed in the painting.